CONFIDENCE WITH SHOOTING RESULTS IN FUTSAL EXTRACURRICULARS - Muhammad Aldi Hutami; Bayu Iswana (Universitas Negeri Gorontalo, 2020)
The purpose of this study was to determine the relationship of the level of self-confidence with the shooting results of Futsal extracurricular participants. This study uses a correlational method that links the variable confidence with shooting results. The population in this study were 20 Futsal extracurricular participants of Palembang State Junior High School 24 in which the entire population was sampled. The test instrument consists of 2 types, namely a questionnaire to measure the level of confidence and skills tests to measure shooting results. Data analysis technique used t test analysis with 95% confidence (p = 0.05). The results showed the correlation coefficient between the level of confidence with the results of the shooting kick was 0.473, with a ratio of r table = 0.444. Hypothesis test results obtained t count is 2.276, with a ratio of t table = 2.101. The conclusion that can be drawn from this study is that there is a positive and significant relationship between self-confidence and shooting results.